Role of clinical history in beta-lactam hypersensitivity. Issue 4 (August 2021) - Plager, Jessica; Judd, Allen; Blumenthal, Kimberly
Abstract : Purpose of Review: Understand how the clinical history has been used to risk stratify patients reporting a beta-lactam allergy, both in clinical care pathways and predictive models. Recent findings: Drug allergy clinical care pathways have emerged as a safe and effective method of stratifying patients with a reported beta-lactam allergy into risk categories, with 'low-risk' patients able to proceed straight to direct challenges or test doses. These methods have streamlined antibiotic stewardship policies and penicillin allergy de-labeling. However, how to define 'low-risk' has been subject to much debate. New research has developed predictive models that utilize the clinical history to assess a patient's true risk of beta-lactam allergy. Summary: The clinical history has long been an essential part of drug allergy evaluation and has proven invaluable within the past decade in the development of drug allergy clinical pathways. Evidence-based predictive models that use the clinical history to assess a patient's true risk of beta-lactam allergy offer tremendous promise, but differ in crucial areas such as the populations they study, the predictor variables they use, and the ultimate accuracy they attain. These models highlight key aspects of the drug allergy history and pave the way for future large-scale research.